2015
DOI: 10.1002/jcc.23914
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigation of crown/ammonium complexes in solution

Abstract: The Gibbs energies of association ΔGsolT between primary alkyl ammonium ions and crown ethers in solution are measured and calculated. Measurements are performed by isothermal titration calorimetry and revealed a strong solvent-dependent ion pair effect. Calculations are performed with density functional theory including Grimme's dispersion correction D3(BJ). The translational, rotational, and vibrational contributions to the Gibbs energy of association ΔGsolT are taken into account by a rigid-rotor-harmonic-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…and Chiu et al . as well as our recent work demonstrated that solvation and the nature of the counterion to also have substantial effects on the association behavior of crown/ammonium complexes and the corresponding pseudorotaxanes. Hence, a solvent‐dependent analysis of ion‐pairing effects on the association processes is included here as well.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…and Chiu et al . as well as our recent work demonstrated that solvation and the nature of the counterion to also have substantial effects on the association behavior of crown/ammonium complexes and the corresponding pseudorotaxanes. Hence, a solvent‐dependent analysis of ion‐pairing effects on the association processes is included here as well.…”
Section: Introductionmentioning
confidence: 76%
“…Althought he structurald ifferences of the two guests G O 2 and G C 2 are small( two ether oxygen atoms in G O 2 insteado ft wo isoelectronic methylene groups in G C 2), they differ significantly with respect to chelate cooperativity.S tudies by Gibsone tal., [39][40][41] Stoddarte tal. [42] and Chiu et al [43] as well as our recent work [44] demonstrated that solvationa nd the nature of the counterion to also have substantial effects on the association behavior of crown/ammonium complexesa nd the corresponding pseudorotaxanes. Hence, as olvent-dependent analysiso fi on-pairing effects on the association processes is included hereasw ell.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The structures were reoptimized with PBE0‐D3/def2‐SVP. We showed in a previous study for other organic complexes that the use of a double‐ ζ basis set is sufficient for this purpose …”
Section: Methodsmentioning
confidence: 99%